Variability in Baseball Throwing Metrics During A Structured Long-toss Program: Does One Size Fit All?. Issue 7 (29th July 2019) - Leafblad, Nels; Larson, Dirk; Fleisig, Glenn S.; Conte, Stan; Fealy, Stephen; Dines, Joshua; D'Angelo, John; Camp, Christopher L.
Objectives: The variability of throwing metrics, particularly elbow torque and ball velocity, during structured long-toss programs is yet to be fully elucidated. The primary aims of this study were to assess various throwing metrics through a structured long-toss program using wearable technology and to quantify the intra and inter thrower variability of these metrics at each stage of throwing. Methods: This was a descriptive laboratory study in which 60 high school and collegiate pitchers participated in a predetermined, structured, progressive long-toss program. All players wore a motusBASEBALL sleeve (Motus Global, Inc.; Rockville Centre, NY), which measured arm slot, arm velocity, shoulder rotation, and elbow varus torque. Radar guns were used to measure ball velocity. These metrics were compared within and between all pitchers at each of the following throwing distances: 90 ft, 120 ft, 150 ft, 180 ft, and maximum effort mound pitching. Intra- and inter- thrower reliabilities were calculated for each throwing metric at every stage of the program. Excellent intra-thrower reliability was defined by an Intra-class coefficient (ICC) >0.750. Acceptable inter-thrower reliability was defined by a Coefficient of Variation (CV) <5%. Results: Ball velocity significantly changed at each progressive throwing distance, but this did not consistently correlate with an increase in elbow torque. Pitching from the mound did not place more torque on the elbow than throwing from 120 ft and beyond. Intra-thrower reliability was excellent throughout the progressive long-toss program for each throwing metric. Ninety-one percent of throwers had acceptable inter-thrower reliability for ball velocity, whereas only 79% of throwers had acceptable inter-thrower reliability for elbow torque. Conclusion: Based on trends in elbow torque, it may be practical to incorporate pitching from the mound earlier in the program (once a player is comfortable throwing from 120 ft). Ball velocity and elbow torque do not necessarily correlate with one another, so a degree of caution should be exercised when using radar guns to estimate elbow torque. Given the variability in elbow torque between throwers, some athletes would likely benefit from an individualized throwing program.